Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Es Teh Indonesia (Survei Pada Followers Twitter Es Teh Indonesia) - Fauzi, Afry Zihan; Maulana, Asep (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study analyses the effect of Brand Image and Product Quality on Purchasing Decisions on Es Teh Indonesia products using a sample of 309 respondents randomly selected through the random sampling method from followers of the Es Teh Indonesia Twitter account. The population in this study refers to all followers of the Es Teh Indonesia Twitter account. The analytical method used is descriptive-verification with path analysis using the Successive Interval Method (MSI), and supported by Microsoft Excel 2019 and SPSS version 23. The results showed a low correlation between Brand Image and Product Quality (0.397), as well as a significant effect of Product Quality on Purchasing Decisions. However, Brand Image does not have a significant effect partially. Overall, Brand Image and Product Quality simultaneously influence 92.83% of Purchasing Decisions, while 4.5% may be influenced by other factors that have not been studied.